Análises econômicas e saúde do adolescente: revisão da literatura no período de maio de 2006 a abril de 2008: Economic analysis and adolescent health: a literature review from May 2006 to April 2008 - Arinelli Fernandes, Roberta; Ribeiro de Souza, Camila Pepe (Adolescência e Saúde, 2009)
The high prevalence of chronic diseases, the development of new health techniques and the scarcity of financial resources make economic studies become more frequent. A review and a critical analysis of the literature were done correlating health economics and adolescent health, from May 2006 to April 2008, in Medline, Cochrane and LILACS database. Twenty-five articles were selected. The most found speciality was mental health and the most found pathology was asthma. The result reflects a scarcity of publications in this area.